Risk-Based assessment concept and its application towards pipeline integrity - Khadijah Abdul Razak, author; Norhazilan Md. Noor, author; Nordin Yahaya, author; Shadiah Husna Mohd.Nor, author; Proceeding in EnCon2008 Engineering Conference on Sustainble Engineering Infrastructures Development & Menagement (18 : Kucing, Saraak) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL